Uso e ocupação do solo em áreas de assentamentos rurais no norte de Minas Gerais - Rodrigo Praes de Almeida (2015)
The environmental changes resulting from human activity have occurred since the nineteenth and twentieth centurys, with increasing usage rates and occupancy irreconcilable with the carrying capacity of natural ecosystems, as well the environment is changed, and consequently, the various transformations occurred. There are numerous discussions on the scope of the agrarian reform and the economic and environmental viability of rural settlements. Thus, the aim of this study was to compare the use and occupation of land in settlement areas in the North region of the Minas Gerais State in 2003 and 2014 and evaluate the soil chemical properties after eleven years of use of areas Agricultural production. The settlements were selected Paco Paco, Poço da Vovó and Bom Sucesso, located in the cities of Pirapora, Jaíba and Verdelândia, respectively. A database was created for the spatial analysis of the images, it was later made the selection of areas of interest through the images of Landsat 5 and Landsat 8 satellite, TM and OLI sensors, respectively, and finally was held supervised classification which was used Bhattacharya classifier algorithm, the program used in this study Spring 5.3. Thereby, they were generated thematic maps of land use and occupation to compare the evaluated years, it was possible to assign 3 classes in the classification training (native vegetation, crops and soil exposed). Alongside a soil sample was collected in each land use class and certain chemical attributes with pH, Ca, Mg, K, P, Al, H+Al, SB, t, T, m and V in 2 soil depths (0-20 e 20-40cm). These results were submitted to analysis of variance and treatment means were compared by Tukey test (p <0,05) using the R program. The settlement Bom Sucesso had a decrease of 68 ha in the areas of vegetation native, an increase of 10,2 ha in the areas of crop and 56,3 ha in the areas of exposed soil. The Paco Paco settlement had a decrease of 171 ha in the area of native vegetation and an increase of 60,3 ha in the areas of crop and 23,5 ha in the areas of exposed soil. The Poço da Vovó settlement had a decrease of 911,5 ha in the area of native vegetation, an increase of 12,6 ha in the areas of crop and 657,6 ha in the areas of exposed soil. On the accuracy of the classification analysis, it was observed a satisfactory Kappa index for the settlements analyzed, and therefore qualified to perform environmental analysis. According to the obtained results it can be inferred that rural settlements had significant change in land use in the range of 11 years. Soil fertility improved the topsoil (0-20 cm) of the areas occupied by crops and were well managed. The indicators used in this study may be used as a model for the evaluation of soil areas of rural settlements in the north region of the Minas Gerais.